Penerapan Model Pembelajaran Sosiokognitif Berbantuan Multimedia Interaktif Dalam Meningkatkan Hasil Belajar Menulis Teks Deskripsi Pada Kelas IV A SD Inpres Minasa Upa - Tri Suci Mahadaniyah; Aliem Bahri; Sri Rahayu (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
The main problem in this research is how to apply the sociocognitive learning model to improve the learning outcomes of writing descriptive text for class IVA students at SD Inpres Minasa Upa. This research aims to describe the application of a sociocognitive learning model assisted by interactive multimedia in improving the learning outcomes of writing descriptive text for class IVA students at SD Inpres Minasa Upa. This type of research is class action research (Class Action Research) which consists of two cycles where each cycle is carried out in three meetings including a cycle evaluation. Research procedures include planning, implementing actions, observing and reflecting. The subjects in this research were 31 class IVA students at SD Inpres Minasa Upa. The results of the research showed that in the first cycle, of the 31 students who completed individually, only 17 students or 55% met the minimum completion criteria (KKM) or were in the low category. Classically it has not been met because the average value obtained was 59.90. Meanwhile, in cycle II, out of 31 students, 26 people or 81% had fulfilled the KKM and classically had been met, namely the average score obtained was 84.41 or was in the high category. Based on the research results above, it can be concluded that the results of learning to write descriptive text for class IVA students at SD Inpres Minasa Upa through the application of the sociocognitive learning model assisted by interactive multimedia have increased.